2022
DOI: 10.1093/jnen/nlac101
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological findings in COVID-19: an autopsy cohort

Abstract: The literature regarding the neuropathological findings in cases of SARS-CoV-2 infection, which causes coronavirus disease 2019 (COVID-19), is expanding. We identified 72 patients who died of COVID-19 (n = 48) or had recovered shortly before death (n = 24) and had autopsies performed at our institution (49 males, 23 females; median age at death 76.4 years, range: 0.0–95.0 years). Droplet digital polymerase chain reaction (ddPCR) for the detection of SARS-CoV-2 was performed (n = 58) in multiple brain regions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Although APP leakage has been described in brains of subjects that died after hypoxic or ischemic events, the typical pattern of hypoxic APP leakage is not observed in this case [ 40 ]. Post-mortem indications for axonal injury (including positive APP staining) have also been described in three cases with a recent COVID-19 infection, but we did not observe other acute pathologies related to COVID-19, such as hemorrhagic lesions or microvascular injury [ 41 , 42 ]. APP positivity has also been reported after traumatic diffuse axonal injury, or exposure to multiple blast injuries, even years after the injury [ 40 , 43 45 ].…”
Section: Discussionmentioning
confidence: 49%
“…Although APP leakage has been described in brains of subjects that died after hypoxic or ischemic events, the typical pattern of hypoxic APP leakage is not observed in this case [ 40 ]. Post-mortem indications for axonal injury (including positive APP staining) have also been described in three cases with a recent COVID-19 infection, but we did not observe other acute pathologies related to COVID-19, such as hemorrhagic lesions or microvascular injury [ 41 , 42 ]. APP positivity has also been reported after traumatic diffuse axonal injury, or exposure to multiple blast injuries, even years after the injury [ 40 , 43 45 ].…”
Section: Discussionmentioning
confidence: 49%
“…However, the COVID-19 decedents did not have more severe axonal damage than the non-COVID-19 pneumonia control patients alone. Multiple other studies also did not observe damage specific to COVID-19, as the histological findings were typically age-related ( Eschbacher et al, 2022 , Serrano et al, 2021 ), were similar to abnormalities observed in non-COVID-19 severely ill patients ( Gelpi et al, 2023 ), and corresponded with sequelae of critical illness or treatment ( Gelpi et al, 2023 , Normandin et al, 2023 , Eschbacher et al, 2022 ). These studies did not find clear evidence of viral infection of the brain, which is in line with many studies failing to detect viral protein in most COVID-19 decedents ( Agrawal et al, 2022 , Fabbri et al, 2022 , Gelpi et al, 2023 , Normandin et al, 2023 , Ruz-Caracuel et al, 2022 , Khan et al, 2022 , Khan et al, 2021 , Eschbacher et al, 2022 , Serrano et al, 2021 ).…”
Section: Resultsmentioning
confidence: 86%
“…Multiple other studies also did not observe damage specific to COVID-19, as the histological findings were typically age-related ( Eschbacher et al, 2022 , Serrano et al, 2021 ), were similar to abnormalities observed in non-COVID-19 severely ill patients ( Gelpi et al, 2023 ), and corresponded with sequelae of critical illness or treatment ( Gelpi et al, 2023 , Normandin et al, 2023 , Eschbacher et al, 2022 ). These studies did not find clear evidence of viral infection of the brain, which is in line with many studies failing to detect viral protein in most COVID-19 decedents ( Agrawal et al, 2022 , Fabbri et al, 2022 , Gelpi et al, 2023 , Normandin et al, 2023 , Ruz-Caracuel et al, 2022 , Khan et al, 2022 , Khan et al, 2021 , Eschbacher et al, 2022 , Serrano et al, 2021 ). However, viral protein has been found in the brainstem ( Matschke et al, 2020 ) and viral antigen has been detected in cells expressing the ACE2-receptor – a receptor known for the SARS-CoV-2 virus to bind ( Beyerstedt et al, 2021 ) – in the vascular compartment ( Schwabenland et al, 2021 ).…”
Section: Resultsmentioning
confidence: 86%
“…This manifested as punctate and linear hypointensities on susceptibility-weighted imaging (SWI), which may correspond to the perivascular “ball-and-ring” hemorrhages reported in the pathology literature. 51 52 Microhemorrhages have mainly been reported in the corpus callosum and subcortical and deep hemispheric white matter ( Fig. 6 ).…”
Section: Vascular Inflammatory Conditions and Coagulopathymentioning
confidence: 99%